A novel bridgeless interleaved-based dual-output boost-type PFC rectifier - Monteiro, Vítor Duarte Fernandes (2023)
Power factor correction (PFC) rectifiers is an old topic of research, which is assuming extra applicability to alleviate power quality complications in modern power grids. In this background, this paper proposes a novel PFC rectifier, which has as core differentiating characteristics the bridgeless structure, the interleaved current control, the operation with three voltage levels, and the dual output voltage. The proposed PFC rectifier works as a boost voltage topology, but offering an asymmetrical split dc-link, which can be advantageous in many applications as an AC-DC front-end converter. For all power range, the proposed PFC rectifier ensures a sinusoidal AC current in phase with the voltage, and controlled dc-link asymmetrical voltages. The paper outlines a broad clarification of the proposed topology, the operation principle, the employment of the control theory, and a set of computational results, attained with an AC voltage of 230 V - 50 Hz and a split DC-link voltage stabilized at 400 V. The proof of the topology and control of the proposed PFC rectifier is performed in steady-state, and also for sudden variations of the operation power.